Analysis and development of sipemas: community complaint applications using the rapid application development method - Eugenius Kau Suni; Denny Jean Cross Sihombing (Jurnal Mantik, 2023)
This research investigates the implementation of the Rapid Application Development (RAD) method for creating the "Sipemas" public complaint application to enhance user engagement and government responsiveness. Through comprehensive surveys and direct interactions with "Sipemas" users, the study demonstrates the efficacy of the RAD approach in designing and developing an application that aligns with user expectations and needs. The research findings highlight the positive user response to critical features such as mobile-based complaint submission and real-time status tracking, indicating the significance of accessibility and transparency in public service interactions. The iterative development process facilitated by RAD allowed for the creation of refined functional prototypes based on user feedback, contributing to an application that offers a tailored user experience. Despite challenges such as optimizing performance for various devices and user preferences for complaint status notifications in "Sipemas," the study concludes that the RAD methodology successfully delivered a responsive and user-centered application. The research contributes valuable insights into the application of RAD in public service technology development and guides similar initiatives in the future. Overall, this study underscores the importance of agile methodologies like RAD in addressing complex challenges and improving public service responsiveness through innovative technology solutions.